IMPLEMENTASI PEMBUATAN KAWASAN RUMAH PANGAN LESTARI GAMPONG SUAK PANDAN KECEMATAN SAMATIGA KABUPATEN ACEH BARAT - Khairunnas Khairunnas; Susy Sriwahyuni; Arif Iskandar; Azwar Azwar (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2021)
The problem of malnutrition in families, especially in infants, is a public health problem since long time ago. The economic crisis that has occurred since 1997 until now has not been properly addressed. This causes the number of poor families to increase and the purchasing power of food decreases. Furthermore, the availability of food in the family becomes limited which in turn has the potential to cause malnutrition and even malnutrition. Malnutrition is a major factor causing infant and toddler deaths. Nutrition problems are generally caused by two main factors, namely disease infection and low nutritional intake due to lack of food availability at the household level or wrong care patterns. The problem of malnutrition and malnutrition in children under five is a problem that needs to be addressed. The purpose of this service is the implementation of a sustainable food house model in the village of view in the district of Samatiga, West Aceh Regency. The food house provides information on diet and insight into the effects of malnutrition on infants. The dedication method is by triggering a restaurant to get information and comprehensive insight about eating patterns in children under five who have the potential to experience malnutrition. The results of devotion are able to form eating patterns in groups and are able to form malnutrition prevention behaviors in toddlers in Suak Pandan village.